(untitled) (Piwulang: Jurnal Pendidikan Bahasa Jawa, 2024)
The purpose of this study was to explain (1) Find and describe the types of skin diseases and their treatments in Serat Dayasarana; and (2) Find the types of treatment materials and validation of treatment materials in Serat Dayasarana. The research method used is content analysis method with the research data source of Serat Dayasarana text. Data collection in this study was done using the read-and-record method. The validity used in this research is semantic validity and confirming the results of the analysis on the results of research related to skin diseases and their treatment. The results of this study found four types of skin diseases like bisul, kudis, kadas, and borok. The ingredients used to treat the four diseases include jarak, kenanga, kamijara/sereh, sambilata, adas, pulasari, sulfur, terusi, coconut oil, kesambi leaves, sangkobak, and cucumber. These ingredients are scientifically validated for the treatment of skin diseases.